Identity-based ring signature scheme with multi-designated verifiers. (12th May 2023) - Qu, Yunyun; Zeng, Jiwen
As far as we know, there is only one ring signature scheme with multi-designated verifiers in the literature and the scheme is based on the bilinear pairings which need to consume a lot of computation and under the traditional public key infrastructure (PKI). In order to improve computational efficiency and solve the problem of certificate management in PKI, in this paper, we propose the first identity-based ring signature scheme with multi-designated verifiers without pairings. We prove that our novel scheme's unforgeability, anonymity in the random oracle model and indistinguishability in the standard model under the intractability assumption of discrete logarithm problem and decisional Diffie-Hellman problem, and we prove that our novel scheme's non-transferability in the standard model. We compare the new scheme with a previous scheme in terms of computation and communication at last. The results show that our new scheme is more efficient than the previous scheme and is more suitable for the multi-user setting.